Disruption of dopamine homeostasis has sexually dimorphic effects on senescence characteristics of Drosophila melanogaster - Bednářová, Andrea; Hanna, Marley E; Rakshit, Kuntol; O'Donnell, Janis M; Krishnan, Natraj (The European journal of neuroscience, 2017)
The neurotransmitter dopamine (DA) is known to be involved in a multitude of physiological processes. We investigated sexually dimorphic effects of disruptions in DA homeostasis and its relationship to senescence using three different Drosophila melanogaster mutants namely Catsup (Catsup26 ) with elevated DA levels, and pale (ple2 ), Punch (PuZ22 ) with depleted DA levels. In all genotypes including controls, DA levels were significantly lower in old (45-50-day-old) flies compared with young (3-5-day-old) in both sexes. Interestingly, females had lower DA content than males at young age whereas this difference was not observed in old age, suggesting that males had a larger decline in DA levels with age. Females, in general, were longer lived compared with males in all genotypes except ple2 mutants with depleted DA levels. This phenotype was abolished in the ple2 rescue flies. Interestingly, females also demonstrated marked age-related decline in circadian locomotor activity compared with males. Old Catsup26 males with elevated DA levels accumulated significantly lower levels of lipid peroxidation product 4-hydroxy 2-nonenal (4-HNE) compared with age-matched wild type, ple2 and PuZ22 mutant males. In Catsup26 revertant lines this phenomenon was absent. We also observed a sexually dimorphic response in the expression levels of key stress and aging associated and/or related transcription factor genes across genotypes with elevated or depleted DA levels which was reverted to wild type levels in specific rescue lines. Taken together, our results reveal a novel sexually dimorphic involvement of DA in senescence characteristics of D. melanogaster.
Keywords: homeostáza; Circadian Clocks; 4-hydroxynonenal; Drosophila melanogaster; Drosophila Proteins; Male; Aging; proteiny Drosophily; protein carbonyl; Genotype; sexuální faktory; Homeostasis; mužské pohlaví; dopamin; lokomoce; lifespan; Dopamine; Animals; Locomotion; ženské pohlaví; circadian rhythms; zvířata; Sex Factors; stárnutí; peroxidace lipidů; genotyp; Lipid Peroxidation; Female; aging; cirkadiánní hodiny